Protective effect of MOTILIPERM in varicocele-induced oxidative injury in rat testis by activating phosphorylated inositol requiring kinase 1α (p-IRE1α) and phosphorylated c-Jun N-terminal kinase (p-JNK) pathways. (1st January 2018) - Soni, Kiran Kumar; Zhang, Li Tao; Choi, Bo Ram; Karna, Keshab Kumar; You, Jae Hyung; Shin, Yu Seob; Lee, Sung Won; Kim, Chul Young; Zhao, Chen; Chae, Han-Jung; Kim, Hye Kyung; Park, Jong Kwan
Abstract: Context: MOTILIPERM was prepared as a mixture of extracts of three medicinal herbs [roots of Morinda officinalis How (Rubiaceae), outer scales of Allium cepa L. (Liliaceae) and seeds of C uscuta chinensis Lamark (Convolvulaceae)]. Objective: To investigate the role of reactive oxygen species (ROS)-based endoplasmic reticulum (ER) stress in a rat model of varicocele and the therapeutic efficacy of MOTILIPERM in this model. Materials and methods: Sixty male rats were divided into five experimental groups: a normal control group (CTR + vehicle), a control group administered MOTILIPERM 200 mg/kg (CTR + M 200), a varicocele-induced control group (VC + vehicle) and two varicocele-induced groups administered MOTILIPERM 100 (VC + M 100) or 200 (VC + M 200) mg/kg for 4 weeks. Testis weights were recorded and serums were assayed for hormone concentrations. Tissues were subjected to semen analysis, histopathology, analyses of ER response protein expression levels and oxidative stress were assessed by measuring ROS, reactive nitrogen species (RNS), malondialdehyde (MDA) level and ratios of total glutathione (GSH)/oxidized GSH (GSSG). Results: MOTILIPERM treatment of varicocele-induced groups significantly increased left testis weight, testosterone level, sperm motility, count and spermatogenic cell density. ER-response protein expression levels were dose-dependently decreased in VC + M 200 group compared with VC + vehicle group. MOTILIPERM treatment also decreased MDA and ROS/RNS level but increased GSH/GSSG ratio. Discussion and conclusions: This study suggests that ROS-related ER stress may play a major role in varicocele-induced infertility and MOTILIPERM, a novel compound targeting ROS-based ER stress, may be therapeutically useful in treatment of varicocele, or as a supplement for the treatment of infertility.